Kepemimpinan Transformasional dalam Masa Krisis: Studi Penanganan COVID-19 di Bumi Raja-Raja - Fitriati, Rachma; Marsanty, Dea Alita (Research and Development Agency Ministry of Home Affairs, 2023)
This study aims to analyze the transformational leadership of Village Heads in efforts to break the chain of the spread of COVID-19 in the Maluku Province area known as Bumi Raja-Raja. Village heads are called